Microbiome Associated with Olive Cultivation: A Review - Rogério Melloni; Elke J. B. N. Cardoso (Plants, 2023)
International research has devoted much effort to the study of the impacts caused to the soil by different management practices applied to olive cultivation. Such management involves techniques considered conventional, including the control of spontaneous plants with herbicides or machines, inorganic fertilizers, and pesticides to control pests and diseases. Equally, some producers use sustainable techniques, including drastic pruning, the use of cultivars that are tolerant to diseases and adverse climates, the use of organic conditioners in the soil, the maintenance of vegetation cover with spontaneous plants, and the use of inoculants, among others. In both conventional and sustainable/organic management, the effects on soil quality, crop development, and production are accessed through the presence, activity, and/or behavior of microorganisms, microbial groups, and their processes in the soil and/or directly in the crop itself, such as endophytes and epiphytes. Thus, our present review seeks to assemble research information, not only regarding the role of microorganisms on growth and development of the olive tree (Olea europaea L.). We looked mainly for reviews that reveal the impacts of different management practices applied in countries that produce olive oil and olives, which can serve as a basis and inspiration for Brazilian studies on the subject.